Reliance of Sovereign Credit Ratings on Governance Indicators - Ozturk, Huseyin (PALGRAVE MACMILLAN LTD, 2016)
This study attempts to provide one of the first comprehensive analyses on the relationship between sovereign credit ratings and governance indicators. The analyses are performed using ordered response models and panel regression techniques. The findings indicate that better governance, measured by six different Worldwide Governance Indicators, is positively associated with higher credit ratings. I also find that sovereign credit ratings significantly respond to the developments in these indicators. These results imply that credit rating agencies remain alert on the quality of governance. This caution sheds doubt on the accuracy of sovereign credit ratings since several measures of governance, and Worldwide Governance Indicators in particular, have several weaknesses. This article proposes that credit rating agencies consider employing their internal sources to measure the quality of governance to eliminate reliance on governance indicators.
Keywords: credit rating; governance indicators; developed country; developing country; DEBT; Development Studies